O estudo dos neologismos semânticos no ensino de português: abordagem a partir de textos publicitários - Elida Ferreira Martins (2015)
This work focus itself on the lexical aspect of semantic neologisms and its approach on the portuguese classes on Brazil. The main goal of this paper is to analyze, through a qualitative analysis done from a corpus of advertising texts on a nationwide magazine, the semanticneologisms from a pedagogical perspective. The neologisms corpus is composed by 26 samples of the 2013 Veja magazine in its digital format, covering all editions between january and june. All advertising texts contained on those editions were analiyzed with theintent to find neologisms. The analysis procedure adopted by this research was the selection of some neologisms by a lexicographical criterion having an exclusion corpus of three representative portuguese dictionaries. The analysis of the choosen itens was doneconsidering the occurrence; the advertiser; the meaning assumed on the advetising text in opposition to its original meaning; the kind of semantic neologism, which was classified in stylistic and denominative; and the formation type of the lexical item, which there is 11different types of formations. It was also done a corpus of collected neologisms founded on the advertising texts, which served as a sample of the author´s pedagogical proposals based on didactical procedures suggested by Dolz, Noverraz and Schneuwly. Thus, the author gathers together the lexicon teaching with the text teaching, considering how the work with the contextualized lexical itens contributes to the development of a lexical competence and, therefore, to the development of student´s communicative competence. Within a textual perspective, it´s possible to teach the lexicon without untie it from the meaning productionand dealing with authentic linguistic uses. This research guides itself with relevant aspects of the lexical theory, based on works of prestigious authors like Alves, Bezzera, Biderman and Ferraz, and approaches issues about the lexical productivity, observing effective mechanismsof language renewal. About the teaching methods, researches of Antunes, Bezerra, Bortoni-Ricardo, Dolz, Ferraz, Ilari, Marcuschi, Neves, Noverraz, Schneuwly, and others, were used as paradigms, and the theoretical line adopted is according to the official Braziliangovernment rules about the teaching of portuguese language on schools, emphasizing that those directives can also improve the portuguese language teaching. This paper treats as well about textual genres issues, bringing a wide discussion regarding the advertisement genre.Taking the language in a interacionist perspective, the author tries to demontrate that there is no reason to mantain the marginal treatment given to the lexical component of the language teaching, offering, by combining theory and practice, contributions for future researches andmaterials which aim to the development of student´s lexical competence.